2009
DOI: 10.1038/cgt.2009.30
|View full text |Cite
|
Sign up to set email alerts
|

Novel strategies to augment genetically delivered immunotoxin molecular therapy for cancer therapy

Abstract: Immunotoxin therapy is a promising molecular cancer treatment strategy. Its main advantage is seletive cytotoxicity towards tumor cells and minimal toxicity in normal tissues. However, a short half-life and rapid clearance severely hampers its clinical application. We report here a novel genetic approach in which a recombinant adenovirus vector was used to deliver an immunotoxin gene e23(scFv)-PE40 targeted to the oncogene c-erbB-2 (also known as Her2/neu). This vector, when combined with a low dose of a condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…staining by both commercial rabbit anti-P2X 3 antibody and DyLight ® 594-labelled rabbit anti-P2X 3 scFv antibody). Moreover, as the DyLight ® 594-labelled rabbit anti-P2X 3 scFv antibody shared a similar staining pattern with commercial anti-P2X 3 antibody and data published previously [39][40][41], it can be concluded that MH7C effectively binds to both human-and rat-expressed P2X 3 .…”
Section: Discussionsupporting
confidence: 59%
“…staining by both commercial rabbit anti-P2X 3 antibody and DyLight ® 594-labelled rabbit anti-P2X 3 scFv antibody). Moreover, as the DyLight ® 594-labelled rabbit anti-P2X 3 scFv antibody shared a similar staining pattern with commercial anti-P2X 3 antibody and data published previously [39][40][41], it can be concluded that MH7C effectively binds to both human-and rat-expressed P2X 3 .…”
Section: Discussionsupporting
confidence: 59%
“…Ad5/3‐BPSA‐ONC EGFR is to the best of our knowledge the first oncolytic virus encoding an immunoRNase or, more generally, immunotoxin. A replication‐deficient Ad vector encoding an active Pseudomonas exotoxin‐based, Her2‐specific immunotoxin has been reported previously . This study did not report whether immunotoxin expression affected vector production, as it was the case for Ad5‐CMV‐ONC EGFR in our study.…”
Section: Discussionmentioning
confidence: 59%
“…Correspondingly, Liu et al . did not observe an increase in vector‐encoded transgene expression after intramuscular and intravenous coinjection with an oncolytic Ad and an only twofold increase after intraperitoneal coinjection. Certainly, inserting the therapeutic gene directly into the oncolytic Ad genome is the superior approach when aiming at increasing expression of the protein drug from amplified virus genomes.…”
Section: Discussionmentioning
confidence: 69%
“…Another promising strategy is to deliver immunotoxin therapy through gene therapy vectors. Huang et al [ 152 ] evaluated a gene therapy approach designed to express intratumoral therapeutic levels of the e23/PE40 fusion protein to target HER2/neu-expressing tumors. The advantages of gene therapy vectors are that they can mediate continuous and prolonged immunotoxin production and may provide reduced host immune response [ 140,153 ] .…”
Section: From Preclinical Development To Therapeutic Applicationmentioning
confidence: 99%